Joint Forces: The Impact of Intrahousehold Cooperation on Welfare in East African Agricultural Households - Lecoutere, Els; Van Campenhout, Bjorn (Informa UK Limited, 2023)
In low- and middle-income countries, poor cooperation between members of smallholder agricultural households may lead to inefficient allocation of productive resources. This study estimates the causal mediating effects of cooperation between spouses on household welfare and public goods provision in Ugandan and Tanzanian monogamous smallholder coffee farming households. The random encouragement to participate in an intensive training program coaching couples in farming as a household enterprise and participatory intrahousehold decision making, which stimulates cooperation and, in turn, household welfare and public goods provision, enables estimating causal mediating effects while avoiding challenges of endogeneity. Spousal cooperation has positive mediating effects on household welfare, measured by total household income per capita and food security, and on household public goods provision, measured by the adoption intensity of agronomic practices and use of improved seed for food crops. Spousal cooperation has larger effects on total household income per capita with longer duration of marriage.